The Uruguay Round : implications for U.S.-Caribbean trade - McDonald, Vincent R. (2000)
Assesses the arguments, pro and con, regarding the likely impact of the interpretation of the provisions of the UR on CARICOM in its dealings with the United States. Estimates the potential welfare impact of the proposed tariff and non-tariff provisions of the Uruguay Agreement as it relates to U.S.-Caribbean trade. Concludes that tariff reductions proposed under the Uruguay Agreement will lead to welfare gains by both trading partners over the short and long run periods - although the U.S. will be the primary beneficiary.